What is there to drink? Water (in)justice in the democratic South Africa - Mbana, Zenande; Sinthumule, Ndidzulafhi Innocent (Frontiers in Water, 2024)
Aligned to Chapter 2 of the Constitution of the Republic of South Africa which recognises water to be a basic human right, the democratic government from 1994 adopted policies, legislation and programmes that encourage universal access to basic water services. Although some progress has been made in urban areas concerning access to potable water supply, South Africa still faces serious problems in providing basic water services in rural areas. This study aims to understand sources of drinking water, how water is accessed by local communities, and determine the barriers associated with access to potable water and management in the rural villages of Madiba and Enqabeni. To fulfil the aim of this study, semi-structured interviews, interviewer-administered questionnaires, and field observations were employed as data collection tools. Data obtained from interviews were analysed using thematic content analysis, while the questionnaires were assessed using Statistical Package for Social Sciences. The study found that the majority of people still rely on untreated water from open water bodies. The study also identified corruption, and infrastructural and institutional problems as barriers affecting water service delivery to communities. These institutional problems mean that water resource management and access are unfair, inequitable and unjust, and constitute water injustice. The basic human right of access to water by communities is thereby violated and this has devastating effects on the lives and livelihoods of community members. Despite democracy, the legacy of apartheid's unequal water policy is still influencing water services and South Africa remains far from achieving Sustainable Development Goal 6.